Ergonomically Oriented Work Methods Reducing Musculoskeletal Complaints of Tofu Factory Workers in Tonja Village - Maytadewi Negara, Ni Luh Gede Aris; Astiti Suadnyana, Ida Ayu; Listiantari, Dwi Astutik (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2021)
Industrial activities develop from all sectors, both formal and informal sectors. The informal sector has an important role in developing countries including Indonesia. Every type and place of work for both formal and informal workers has a risk of hazards that can cause occupational accidents and occupational diseases. In the tofu production process, there are activities that pose a risk of occupational disease and occupational accidents, so choosing the right work method is very important to ensure the health of workers. This research was conducted to determine whether the ergonomically oriented work method in the process of making tofu can reduce musculoskeletal complaints in workers. The research was designed with the same subject design (treatment by subject design). The research was conducted at the Tofu Factory located in the Tonja Village, Bali in September 2020. Sample were seven workers in the tofu factory. The difference in conditions before and after activities using non-ergonomically oriented work methods and ergonomically oriented work methods were compared and statistically tested. The comparative test was carried out on the musculoskeletal complaint score. The results showed that the ergonomically oriented work method caused a decrease in the score of musculoskeletal complaints by 40.03% (p<0.05). It can be concluded that ergonomics-oriented work method significantlyreduced musculoskeletal complaints of the tofu factory workers in Tonja Village.